The Effect of Sales Growth and Capital Intensity on Tax Avoidance in Property and Real Estate Companies - Andoko Andoko (Jurnal Penelitian Akuntansi (JPA), 2022)
Taxes are one of the most crucial instruments in Indonesia. Indonesia's main income derives from taxes collected by local governments and used by the government to spend on state development such as the development of infrastructures and other needs of the state. Company is one of the state’s highest tax contributors. However, the amount of tax paid by the company is calculated as the company's burden. The company's main goal is to maximize net profit. Therefore, the company strives to minimize tax payments through tax avoidanceThis research aims to determine the effect of sales growth and capital intensity on tax avoidance in Property and Real Estate companies listed on the Indonesia Stock Exchange within the period of 2019-2020.The analysis of this research uses SPSS 26.0 to run the multiple linear regression analysis. Result depicts that sales growth has no effect on tax avoidance partially, capital intensity has no effect on tax avoidance partially, and sales growth and capital intensity have an effect on tax avoidance simultaneously.